Organelle perturbation in Alzheimer’s disease: do intracellular amyloid-ß and the fragmented Golgi mediate early intracellular neurotoxicity? - Lou Fourriere; Paul A. Gleeson (Frontiers in Cell and Developmental Biology)
Alzheimer’s disease is a devastating and incurable neurological disease. Most of the current research has focused on developing drugs to clear the extracellular amyloid plaques in the brain of Alzheimer’s disease patients. However, this approach is limited as it does not treat the underlying cause of the disease. In this review, we highlight the evidence in the field showing that the accumulation of intracellular toxic amyloid-ß could underpin very early events in neuronal death in both familial early-onset and sporadic late-onset alzheimer’s disease. Indeed, intracellular amyloid-ß, which is produced within intracellular compartments, has been shown to perturb endosomal and secretory organelles, in different neuronal models, and the brain of Alzheimer’s patients, leading to membrane trafficking defects and perturbation of neuronal function associated with cognition defects. The Golgi apparatus is a central transport and signaling hub at the crossroads of the secretory and endocytic pathways and perturbation of the Golgi ribbon structure is a hallmark of Alzheimer’s disease. Here, we discuss the role of the Golgi as a major player in the regulation of amyloid-β production and propose that the Golgi apparatus plays a key role in a cellular network which can seed the onset of Alzheimer’s disease. Moreover, we propose that the Golgi is central in an intracellular feedback loop leading to an enhanced level of amyloid-β production resulting in early neuronal defects before the appearance of clinical symptoms. Further advances in defining the molecular pathways of this intracellular feedback loop could support the design of new therapeutic strategies to target a primary source of neuronal toxicity in this disease.